Deep touch pressure for calming and comfort therapy from the perspective of contact mechanics: A review - Mohamad Izzur Maula; Tri Indah Winarni; Muhammad Imam Ammarullah; Ilham Yustar Afif; Farhan Ali Husaini; M. Danny Pratama Lamura; Jamari Jamari (Universitas Muhammadiyah Magelang, 2023)
The art of touch therapy has been around for centuries and has evolved into various models and styles throughout the years. In addition to reducing muscle pain, relieving stress, and providing relaxation, this therapy has worked and has been useful for many people. Methods such as touch or pressure stimulate the parasympathetic nervous system, which plays a role in a person's emotional well-being. Knowing its effects, the interaction between therapeutic devices used on the body needs to be studied further. The contact area provided by the deep touch pressure (DTP) tool will also play an important role in the therapeutic outcome. In addition, levels of comfort in pressure treatment should also be explored further to ensure compliance. This paper describes in extensive the potential of DTP in providing a comfort effect from a contact mechanics perspective. Interactions of various DTP types and pressure distribution on body area have been further investigated to minimize the contact mechanics research gap in DTP and provide the bridge between sensory therapy and the mechanical engineering domain.